Pressure drop performance in gas custody transfer through domestic gas meter operations - Mohsin, R. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
Ranked 12th in the world for its natural gas reserves, standing with 82.5 trillion metric standard cubic feet, Malaysia, has certainly emerged as a major exporter and gas user globally. It was only lately in December 1984 that Petronas Gas Bhd. (PGB) started a pilot project to supply piped in natural gas in Terengganu which eventually marked the beginning of the Peninsular Gas Utilisation (PGU) project. The noble aim of the project was to bring natural gas from our offshore fields to the consumers. In line with this, Malaysia has attained and thus practicing the knowledge of gas transmission and distribution. At present, the increasing number of gas domestic customer either employing Natural Gas (NG) or Liquefied Petroleum Gas (LPG) as their burning fuel has driven attention towards accuracy of gas transfer. Losses to custodian may have significant impact in terms of monetary returns. This type of losses may be directly related to the effect of measurement accuracy and pressure losses. Therefore there is a need to study pressure performance in low flowrate gas system in the domestic sector. In this particular research work, indigenous technology to construct a domestic gas meter calibrator has found its lead by establishing a prototype calibrator. A development of a scale model flow system using domestic gas meters, the pressure losses performance can be monitored carefully and could lead to the formulation and understanding of the pressure capacity and its consequence effect to the metering accuracy. Bench tests ofthis prototype has proven a great success and reliable. This is also in line with SIRIM initiative to establish standards in the domestic gas meter applications.